2021
DOI: 10.1007/s00520-020-05948-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 precautionary behavior among Israeli breast cancer patients

Abstract: Objective Cumulative knowledge indicates that cancer patients, among them breast cancer patients, are more susceptible to COVID-19 than individuals without cancer. Therefore, these patients need to take additional precautions against the COVID-19 outbreak. This study aimed to examine factors associated with precautionary behavior among Israeli breast cancer patients during the COVID-19 pandemic. Methods A cross-sectional study was conducted among 151 women with breast cancer. Participants completed measures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…In particular, COVID-19 was an important psychosocial stressor for women with breast cancer [10]. This is because breast cancer mortality can be exacerbated by COVID-19, and women with breast cancer are more susceptible to and may therefore be more cautious of COVID-19 [11]. Yet, the COVID-19 pandemic has thwarted the provision of effective and supportive care for women with breast cancer, who are further at risk of infection due to immunosuppressive malignancy [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, COVID-19 was an important psychosocial stressor for women with breast cancer [10]. This is because breast cancer mortality can be exacerbated by COVID-19, and women with breast cancer are more susceptible to and may therefore be more cautious of COVID-19 [11]. Yet, the COVID-19 pandemic has thwarted the provision of effective and supportive care for women with breast cancer, who are further at risk of infection due to immunosuppressive malignancy [12].…”
Section: Introductionmentioning
confidence: 99%
“…The results of one study conducted in Turkey reported that women who survived breast cancer were left with problems with their physical, emotional, cognitive and social functioning during the COVID-19 pandemic [14]. Israeli women with breast cancer during the COVID-19 pandemic had a good understanding of health, a high level of knowledge about COVID-19, and a moderately perceived threat of it [11]. Whereas a study in India found that women with breast cancer experienced psychological distress in response to the disease by having anxiety, depression, anger, and guilt [3].…”
Section: Introductionmentioning
confidence: 99%
“…Sense of mastery, defined as a person's confidence in their ability to impact the course and consequences of life events (Infurna & Infurna, 2017 ), was proven to be a crucial internal protective psychological resource after patients perceived threats (Shinan‐Altman & Levkovich, 2021 ). According to the Attribution Theory (Martinko & Mackey, 2019 ), the premise for effectively solving an issue is to identify the influencing elements, which are frequently split into internal and external causes.…”
Section: Introductionmentioning
confidence: 99%